The integration of sport science and coaching: A case study of an American junior record holder in the hammer throw - Judge, L. W.; Judge, M.; Bellar, D. M.; Hunter, I.; Hoover, D. L.; Broome, R.; Neal, A.; Stone, M.; Stone, M. (International Journal of Sports Science & Coaching, 2016)
The purpose of this case study was to describe the integration of sport science and coaching that helped to produce an American junior record of 68.12m in the women's hammer throw in 2012. Two digital video cameras (Canon Elura 60) running at 60 Hz were placed to view Shelby Ashe's best throws at the 2010 USATF Nationals (61.77 m), 2011 USATF Junior Nationals (58.34 m), and 2012 USATF Junior Nationals (68.12m American junior record). Following each competition, the coach collaborated with the sport scientist and chair of USATF coach's education to review and evaluate each of the throws. The record setting throw by Ashe was 1.49 s in duration from right foot lift off and produced a release velocity of 26.8 m/s. During the throw, Ashe spent 50.35% of the duration of the throw in double support. Improvements in technique focused on strategies designed to increase velocity of the head of the hammer. ABSTRACT FROM AUTHOR